De zelfverantwoording van de geest = Phaenomenologie des Geistes - Hegel, Georg Wilhelm Friedrich; Meininger, J.V.; Hahn, Louis C.G. ([Rotterdam] : Futile, 1980)
Bibliotheek François Vercammen
Nederlands
Monografie
Keywords: Hegel; filosofie